Large technical systems in shrinking municipalities – Exploring system reconfiguration of district heating in Sweden. (March 2023) - Magnusson, Dick; Grundel, Ida
Abstract: With this paper we aim to contribute to the field of sociotechnical studies, and more specifically Large Technical Systems (LTSs) to understand what happens in mature systems and how different segments develop. We argue that there is a need to discuss LTSs more heterogeneously to fully grasp how phases of stagnation and drift play out differently. Our focus is on district heating in Swedish municipalities with a shrinking population. As such district heating is an important system for climate measures in Europe and in Sweden it has a long tradition of municipal ownership and strong development. The emphasis is on the ways different district heating systems evolve and how various segments of an LTS develop. We have used a mixed-methods approach and the empirical material in this study builds on municipal documents and annual reports of energy companies, an online survey to energy companies, and qualitative interviews with representatives from energy companies and municipalities. Our results show that private companies are overrepresented in small and shrinking municipalities, and that they develop their business models around small systems to keep them profitable. Instead, municipal owned companies face several challenges concerning capacity, requirements, and economic profitability. From an LTS-perspective, the analysis shows how different actors in the segments adopt different strategies to manage stagnation, leading to segments drifting apart.